KOORDINASI PENERAPAN KEBIJAKAN AEROTROPOLIS DI KECAMATAN KERTAJATI KABUPATEN MAJALENGKA - Ramdhani, Ryan; Nurasa, Heru; Utami, Sawitri Budi (Sekolah Tinggi Ilmu Administrasi Lembaga Administrasi Negara, 2018)
The title of this research is Coordination of Aerotropolis Policy in Kertajati Sub-District, Majalengka District. This research is motivated by the issue of inter-organizational relations in the application of the Aerotropolis policy which is focuses on three aspects; availability of land in accordance with Majalengka District's regional policies, availability of human resource as workforce, and to minimize social conflicts by creating the direction social and cultural transition of communities affected by the development of Aerotropolis areas. Aerotropolis policies arise from the existence of policies from the central government concerning the establishment of airport's location in Kertajati sub district, Majalengka district, West Java. The location establishment of Kertajati Airport has opened many opportunities to West Java province so that the government of West Java can make a policy about